Study of diffusionless and diffusional transformations using in situ cooling and heating techniques in a scanning electron microscope. (26th October 2020) - Kumar, Deepak; Sarkar, Rajdeep; Singh, Vajinder; Kumar, Suraj; Mondal, Chandan; Ghosal, P.
Abstract : In situ electron microscopy can be an effective tool to investigate the underlying science of many transformation mechanisms in materials science. Useful utilization of these experimentations will provide greater insight into many of the existing theories, as microstructural changes can be visualized in real time under some applied constraints. In this study, we have investigated two basic phase transformation phenomena: diffusionless and diffusional mechanisms with the help of in situ cooling and heating techniques in scanning electron microscope (SEM). In situ cooling experiments have been carried out on secondary hardening ultra-high-strength steels to understand the diffusionless transformation of austenite to martensite. Nucleation and growth of the martensites have been observed with cooling in different steps to −194°C. Details of the formation of different variants of martensites in steel were studied with the help of orientation imaging microscopy. Diffusional transformations were studied in terms of oxidation of pure copper in SEM using in situ heating technique. Different heating cycles were adopted for different samples by in situ heating to a maximum temperature of 950°C for the oxidation study. Nucleation of copper oxides and subsequent growth of the copper oxides at different temperatures were studied systematically. Raman spectroscopy and orientation imaging were done to confirm the formation of oxides and their orientations. The thermal cycling phenomenon was replicated inside SEM with heating and cooling and it has been demonstrated how the nature of copper and its oxides changes with the thermal cycle. This article is part of a discussion meeting issue 'Dynamic in situ microscopy relating structure and function'.